Ten years of surveillance of the Yulong plague focus in China and the molecular typing and source tracing of the isolates. - Peng Wang; Liyuan Shi; Fuxin Zhang; Ying Guo; Zhikai Zhang; Hongli Tan; Zhigang Cui; Yibo Ding; Ying Liang; Yun Liang; Dongzheng Yu; Jianguo Xu; et al. (Public Library of Science (PLoS), 2018)
Plague, caused by Yersinia pestis, was classified as a reemerging infectious disease by the World Health Organization. The five human pneumonic plague cases in Yulong County in 2005 gave rise to the discovery of a Yulong plague focus in Yunnan province, China. Thereafter, continuous wild rodent plague (sylvatic plague) was identified as the main plague reservoir of this focus. In this study, the epizootics in Yulong focus were described, and three molecular typing methods, including the different region (DFR) analysis, clustered regularly interspaced short palindromic repeats (CRISPRs), and the multiple-locus variable number of tandem repeats (VNTR) analysis (MLVA) (14+12), were used for the molecular typing and source tracing of Y. pestis isolates in the Yulong plague focus. Simultaneously, several isolates from the vicinity of Yunnan were used as controls. The results showed that during the 10-year period from 2006 to 2016, an animal plague epidemic occurred in 6 of those years, and 5 villages underwent an animal plague epidemic within a 30-km2 area of the Yulong plague focus. Searching for dead mice was the most effective monitoring method in this plague focus. No positive sample has been found in 6937 captured live rodents thus far, suggesting that the virulence of strains in the Yulong plague focus is stronger and the survival time of mice is shorter after infection. Strains from Lijiang, Sichuan and Tibet were of the same complex based on a typing analysis of DFR and CRISPR. The genetic relationship of Y. pestis illustrated by MLVA "14+12" demonstrates that Tibet and Sichuan strains evolved from the strains 1.IN2 (Qinghai, 1970 and Tibet, 1976), and Lijiang strains are closer to Batang strains (Batang County in Sichuan province, 2011, Himalaya marmot plague foci) in terms of genetic or phylogenic relationships. In conclusion, we have a deeper understanding of this new plague focus throughout this study, which provides a basis for effective prevention and control.